E Effect Alkaline Activator Ratio on Porosity Geopolymer Binder Based Umeanyar Slate Stone Powder - Astariani, Ni Kadek (International Journal of Engineering and Emerging Technology, 2021)
This research focuses on the manufacture of geopolymer binder based on Umeanyar slate stone powder (USSP) with alkaline activator sodium silicate (Na 2 SiO 3 ) and sodium hydroxide (NaOH). The effect of alkaline activator ratio on porosity was investigated in this study. USSP geopolymer binder contains SiO 2 (49%), Al 2 O 3 (11%), CaO (11.2%) and uses a NaOH activator with a concentration of 14 M. The proportion of precursor and activator (P/A) are 70%: 30%; 75%: 25%; 80%: 20% and alkaline activator Na 2 SiO 3 : NaOH (SS/SH) were 1: 1; 1.5: 1; 2: 1, by weight. The sample of the specimen is made in the mould of a cylinder with a diameter of 25mm and height of 50 mm and tested at the age of 7 and 28 days. Porosity test according to ASTMC642-06. The porosity test results of the geopolymer binder at the age of 28 days were decreased when the P/A ratio increased and the SS/SH ratio decreased.